Migrant Labour Recruitment Reform in Malaysia: Towards Ethical and Zero-Cost Migration - Choo Chin, Low (Department of Government Studies Universitas Muhammadiyah Makassar, 2020)
The pressures exerted by migrant workers’ countries of origin, regional calls for migrant protection, and global initiatives have pushed the Malaysian government for labour reforms in line with International Labour Organization standards. A weak labour migration mechanism has led to human trafficking, debt bondage, and workers’ exploitation. Since 2018, Malaysia has concluded and renegotiated improved memoranda of understanding (MoUs) with countries of origin to address forced labour and human-trafficking. Reforming the recruitment system is formalised through government-to-government agreements to eliminate agents, enhance ethical recruitment, and adopt a zero migration-cost model. The analysis shows that the newly negotiated MoUs are significant in tackling the issue of irregular migration in three aspects, by including a clause on repatriation, changing to the government recruitment model, and adopting the employer-pays model. This research utilises official documents, media statements, and secondary literature.